Investigation of Geographical Differences of Arabinoxylan in Wheat Grain and Gel Properties of Arabinoxylan/Starch Complexes and In Vitro Digestion - Haixia Wu; Ting Zhou; Ruifeng Ying; Yuanlin Sun (Foods)
With an increasing number of people pursuing a healthy diet, people have gradually realized the significance of adequate dietary fiber in their diets. In this experiment, wheat bran was collected from eight regions in China with different longitudes and latitudes, different altitudes, and average temperatures during the filling period to study the differences in the Arabinoxylan (AX) of wheat bran. The higher the altitude of the wheat production area was, the higher the AX content in the wheat bran was. Therefore, wheat bran from high-altitude production areas was selected for extracting AX. Different proportions of AX were added to wheat starch (WS) to explore the influence of different concentrations of AX on the gelatinization of WS, including the solubility, swelling capacity, rheological properties, and microstructure of the gelatinized products. Among these eight kinds of wheat, the content of total AX accounted for 11.90–15.79% of their dry weight, with the highest content being in wheat from Wuwei, Gansu. Among them, the content of water-soluble AX accounted for approximately 0.85% of their dry weight content. After adding different concentrations of 0.05–2% AX to the WS system, the gel network structure was changed. The starch hydrolysis rate of bread with 2% AX added was the lowest, of which the contents of rapidly digestible starch and slowly digestible starch were 40.02% and 36.61%, and resistant starch was as high as 25.31%. The addition of AX to starch-based foods is helpful for controlling postprandial blood sugar and insulin levels.